The use of scripture in The Imitation of Christ by Thomas a Kempis - J. Huls (Acta Theologica)
This essay investigates the use of Scripture in The Imitation of Christ by Thomas a Kempis. It discusses some of the conditions during the time of its appearance, focussing on the Devotio Moderna as reform movement, the life of Thomas. It then discusses the Imitation and its use of Scripture in detail.